2021
DOI: 10.1021/acs.orglett.1c02112
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Cross-Nucleophile Coupling of β-Allenyl Silanes with Tertiary C–H Bonds: A Radical Approach to Branched 1,3-Dienes

Abstract: Described herein is a distinctive approach to branched 1,3-dienes through oxidative coupling of two nucleophilic substrates, β-allenyl silanes, and hydrocarbons appending latent functionality by copper catalysis. Notably, C(sp 3 )− H dienylation proceeded in a regiospecific manner, even in the presence of competitive C−H bonds that are capable of occurring hydrogen atom transfer process, such as those located at benzylic and other tertiary sites, or adjacent to an oxygen atom. Control experiments support the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…[122] Silyl stabilized cations were proposed to be a key intermediate in the copper catalyzed cross-nucleophile This electrophilic species then undergoes addition to the allene, affording an allylic radical species 246, which following subsequent oxidation to the β-stabilized cation, is readily desilylated to yield 252. [125] Ohfune and co-workers demonstrated that cationic intermediates could be generated from allenyl silanes through the strategic application of π-acid catalysis. Treatment of 253 with a suitable π acid catalyst allows for cyclisation through the nucleophilic acid in a 5endo-dig cyclisation, which following protodemetallation yields a variety of lactones of general formula 254 in excellent enantioselectivities and yields, and moderate to good diastereoselectivities (Scheme 55).…”
Section: Allenyl Silanesmentioning
confidence: 99%
See 1 more Smart Citation
“…[122] Silyl stabilized cations were proposed to be a key intermediate in the copper catalyzed cross-nucleophile This electrophilic species then undergoes addition to the allene, affording an allylic radical species 246, which following subsequent oxidation to the β-stabilized cation, is readily desilylated to yield 252. [125] Ohfune and co-workers demonstrated that cationic intermediates could be generated from allenyl silanes through the strategic application of π-acid catalysis. Treatment of 253 with a suitable π acid catalyst allows for cyclisation through the nucleophilic acid in a 5endo-dig cyclisation, which following protodemetallation yields a variety of lactones of general formula 254 in excellent enantioselectivities and yields, and moderate to good diastereoselectivities (Scheme 55).…”
Section: Allenyl Silanesmentioning
confidence: 99%
“…In this work, a formal 1,3‐dienylation of acidic C−H bonds with β‐allenylsilanes, di‐ tert ‐butyl peroxide 243 (DTBP) undergoes thermal homolysis to generate tert ‐butoxyl radicals 244 , which subsequently abstract a hydrogen from the C(sp 3 )‐H carbon, forming tertiary radical species 245 . This electrophilic species then undergoes addition to the allene, affording an allylic radical species 246 , which following subsequent oxidation to the β‐stabilized cation, is readily desilylated to yield 252 [125] …”
Section: Silyl Alkynesmentioning
confidence: 99%
“…The use of a bulky and electron-rich diazonium salt was crucial to achieve efficient iodine activation, presumably due to the enhanced stability of the aryl radical. Other notable advances in Cu-catalyzed reactions include the following publications: (1) Cu-catalyzed diazidation reactions; 54 (2) Diastereo-and enantioselective oxidative 1,6conjugate addition; 55 (3) C−H amination of 8-aminoquinoline-directed ferrocenes; 56 (4) Cu-catalyzed hydroxymethylation of alkynes with formic acid; 57 (5) Cu-catalyzed synthesis of indolyl benzo[b]carbazoles; 58 (6) Cu-catalyzed tandem cross-coupling and alkynylogous aldol reaction to access exocyclic α-allenols; 59 (7) Tandem Cu-and Rh-catalysis for oxidation of hydrazones and enantioselective cyclopropanation; 60 (8) Cu-catalyzed CF 2 H-substituted 2-amidofurans; 61 (9) Cu-catalyzed annulation of indolyl α-diazocarbonyl to access carbazoles; 62 (10) Cu-catalyzed enantioselective 1,2reduction of cycloalkenones; 63 (11) Cu-catalyzed enantiodivergent alkynylation of isatins; 64 (12) Cu-catalyzed β-lactam formation from oximes and methyl propiolate; 65 (13) Cucatalyzed aminosulfonylation of O-homoallyl benzimidates; 66 (14) Cu-catalyzed multicomponent trifluoromethylphosphorothiolation of alkenes; 67 (15) Cu-catalyzed chloroarylsulfonylation of styrene derivatives; 68 (16) Cu-catalyzed synthesis of 5-carboxyl-4-perfluoroalkyl triazoles; 69 (17) Crossnucleophile coupling of β-allenyl silanes with tertiary C−H bonds to access 1,3-dienes; 70 (18) Cu-catalyzed C(sp 3 )−H functionalization of O-pentafluorobenzoyl ketone oximes; 71 (19) Total regioselectivity of hydrobromination of alkenes controlled by Fe or Cu catalyst; 72 (20) Enantioselective synthesis of trifluoromethyl cyclopropylboronates by Cu catalysis; 73 (21) Cu-catalyzed asymmetric cyclization of alkenyl diynes; 74 (22) Synergistic Ir/Cu catalysis for asymmetric allylic alkylation of oxindoles; 75…”
Section: Reactionsmentioning
confidence: 99%
“…Other notable advances in Cu-catalyzed reactions include the following publications: (1) Cu-catalyzed diazidation reactions; (2) Diastereo-and enantioselective oxidative 1,6-conjugate addition; (3) C–H amination of 8-aminoquinoline-directed ferrocenes; (4) Cu-catalyzed hydroxymethylation of alkynes with formic acid; (5) Cu-catalyzed synthesis of indolyl benzo­[ b ]­carbazoles; (6) Cu-catalyzed tandem cross-coupling and alkynylogous aldol reaction to access exocyclic α-allenols; (7) Tandem Cu- and Rh-catalysis for oxidation of hydrazones and enantioselective cyclopropanation; (8) Cu-catalyzed CF 2 H-substituted 2-amidofurans; (9) Cu-catalyzed annulation of indolyl α-diazocarbonyl to access carbazoles; (10) Cu-catalyzed enantioselective 1,2-reduction of cycloalkenones; (11) Cu-catalyzed enantiodivergent alkynylation of isatins; (12) Cu-catalyzed β-lactam formation from oximes and methyl propiolate; (13) Cu-catalyzed aminosulfonylation of O -homoallyl benzimidates; (14) Cu-catalyzed multicomponent trifluoromethyl­phosphorothiolation of alkenes; (15) Cu-catalyzed chloro-arylsulfonylation of styrene derivatives; (16) Cu-catalyzed synthesis of 5-carboxyl-4-perfluoroalkyl triazoles; (17) Cross-nucleophile coupling of β-allenyl silanes with tertiary C–H bonds to access 1,3-dienes; (18) Cu-catalyzed C­( sp 3 )–H functionalization of O -pentafluorobenzoyl ketone oximes; (19) Total regioselectivity of hydrobromination of alkenes controlled by Fe or Cu catalyst; (20) Enantioselective synthesis of trifluoromethyl cyclopropylboronates by Cu catalysis; (21) Cu-catalyzed asymmetric cyclization of alkenyl diynes; (22) Synergistic Ir/Cu catalysis for asymmetric allylic alkylation of oxindoles; (23) Hydrosilylation of alkynes and alkenes with Cu-photocatalysis under continuous flow conditions; (24) Cu-based water oxidation catalysts with consecutive ligand-based electron transfer; (25) Heteroleptic copper-based complexes for energy-transfer processes: E → Z isomerization and tandem photocatalytic sequences; (26) Copper-catalyzed aminoheteroarylation of unactivated alkenes through distal heteroaryl migration; (27) Copper-catalyzed syntheses of multiple functionalized allenes via three-component reaction of enynes; (28) Unified mechanistic concept of the copper-catalyzed and amide-oxazoline-directed C­(sp 2 )–H bond functionalization; (29) Cu-catalyzed C–H allylation of benzimidazoles with allenes; (30) Synthesis of 1,2-aminoalcohols through enantioselective aminoallylation of ketones by Cu-catalyzed reductive coupling; (31) Copper-catalyzed N-directed distal C­(sp 3 )–H sulfonylation and thiolation with sulfinate salts; and (32) Dehydrogenative aza-[4 + 2] cycloaddition of amines with 1,3-dienes via dual catalysis …”
Section: Recent Reports On Cu-catalyzed Reactionsmentioning
confidence: 99%
“…The construction of carbon–carbon (CC) bond from readily accessible precursors is of fundamental significance in organic synthesis 1–9 . In this context, transition metal catalyzed stereoselective hydrofunctionalizations of unsaturated CC bonds is a particularly attractive stargate 10–13 .…”
Section: Introductionmentioning
confidence: 99%